THE CORRELATION BETWEEN STUDENTS’ SELF CONFIDENCE AND THEIR SPEAKING SKILL - Teten Mohamad Sapril Mubarok (Institut Pendidikan Indonesia, 2017)
The Corellation between Students’ Self Confidence and Their Speaking Skill. ( In the Second-Grade Students of English Education Department of STKIP Garut) This study was undertaken by the writer because most of English students often got dificulty in English speaking. Especialy in their confident to speak English. To have a good English speaking , the students are expected to be able to build,develop and show their confident to use English speaking in any opportunity. Besides that, through self confident the students costumize to use English as dailly Communication, it is important for the students to get more interaction and practices in English speak in order they can mastering English speaking skill well. This study was aimed at investigating the corellation between students’ self confidence and theirs’ speaking skill. It was intended not only to solve the students dificulties in speaking English, But also to answer the main question “ Is there a significant corellation between students’ self confidence and their speaking skill?”. The writer used the correlational method to find out and investigate whether there was a corellation or not between two variabels and how strong it is. The respondent , Sixty four students of the second grade of English Education Program of STKIP Garut were selected proporsionl stratified randomly. The study began by assigining the students to answer the self confidence questionaries, then the writer collect the students speaking score from first until third which have provided in English program office. Beside that, the writer clasified category for confidennce and took average speaking score from first until third to support the result of the data analysis. The instrument include two variabels: Students’ self confidence and average of speaking score list. To analyze the data, the writer used Pearson/Product Test formula to test the corellation and to test hypotesis. The result of the data analysis showed the coefficient corellation between two variabels is 0,007 (sig = 0,007). Based on this result, it could be concluded that there was a very significant corellation between students’ self confidence and their speaking skill. For this reason, the researcher purposed some recomendation for the teacher and the students of STKIP Garut. The students suggested that they should build, develop,force and show their confidence of practicies in speaking English